PEMBELAJARAN IPS DENGAN MODEL CTL MATERI PERDAGANGAN INTERNASIONAL PADA SISWA IX G SMPN 11 KOTA CIREBON - Leni Herliani; Eulis Henda Nugraha (Universitas Wiralodra, 2020)
This study raises a learning phenomenon in the classroom which is packaged in a Classroom Action Research with the title